P01.21.A Testing Semantic Verbal Fluency (SVFT) in patients with headache suspicious of cancer helps predict those with tumour on imaging. (5th September 2022) - Zienius, K; Hewins, W; Summers, D; McKinlay, L; Brennan, P; Porteous, L; Grant, R
Abstract: Background: Differentiating secondary headache from primary headache on history alone can sometimes be difficult. Headache "plus" other subtle cognitive features improves prediction. Patients and relatives may attribute subtle cognitive or behavioural changes to other causes (e.g. anxiety, low mood). Sematic verbal fluency - "how many animals can you think of in a minute" is commonly impaired on admission in patients with headache harbouring a tumour. We were interested whether SVFT at point of referral for scan would help predict a tumour and requested GPs report the SVFT on electronic referral for direct access scanning in cases with a history of headache suspicious of cancer. The aim of the pilot study was to establish if the SVFT was a "red flag" for secondary causes of headache. We report the results of a 20-month audit of cases. Material and Methods: An electronic Protocol Based Referral (PBR) was developed for Headache Suspicious of Cancer to expedite scanning. The PBR sat alongside the routine e-DACI system that had been in use for some years. The GP was asked to complete the SVFT at the time of referral for scanning. Other data were gathered: PMH cancer; other symptoms/signs; co-morbid conditions and medications. Results: GPs submitted requests for ePBR scanning in 669 cases over 20 months (62% females; Mean age 53: 60% <60 years). SVFT was completed on the request form in 381 (57%) cases. In these cases median SVFT was 17 animals. 11/381 cases were found to have cancer on scanning (2.9%): 10/188 cases with intracranial tumours had a SVFT <17 (5.32%) compared with one with a SVFT >=17. The median SVFT in cases with cancer was 10 animals. Other possible causes of SVFT <17 were - 53 psychiatric or chronic pain conditions on multiple drugs;12 were not native English speakers; 19 had co-existing dementia; 5 had small vessel disease; 4 cysts; 4 Giant Cell Arteritis ; 2 Chiari 1 malformation; PMH - encephalitis (1). Conclusion: A SVFT result <17, at the point of referral for brain imaging, in patients with headache suspicious of cancer was associated with intracranial cancer in more than 1:20 cases, whereas a SVFT of >=17 was associated with cancer in 1:200 cases. SVFT may be an additional useful "red flag". The most appropriate SVFT cut-off requires more research in a larger study. Low SVFT in headache patients may inform Cancer Referral Guidelines, improve the identification of secondary headache and help expedite cases.